Інформаційні віруси в соціальних мережах як засіб інформаційно-психологічного впливу - Мелешко, Єлизавета; Якименко, Микола (Видавництво Львівської політехніки, 2016)
The paper considers the principles when information become viral and types of trust functions of social network agents to new information. It is attempted to formalize concept of informational influence and defense of it by means of concept of ontology.
Keywords: інформаційна безпека; інформаційні віруси; соціальні мережі; пропаганда; національна безпека